MECHANISM OF OLEFIN EPOXIDATION BY VANADIUM(IV) OXO/O2 SYSTEM - YULISTIANA (NIM : 20513004), RISMA
Epoxidation of allyl alcohol and 1-hexene using vanadium(IV) oxo phenoxy-imine as catalyst and O2 as oxidizing agent has been studied. The presence of vanadium(IV) oxo moiety by oxidation of V(III) solution with molecular oxygen of 1 bar was indicated from ʋV=O at 998 cm-1 and λmax at 247 and 757 nm. Phenoxy-imine ligand obtained from corresponding salicylaldehyde and aniline in acidic condition was successfully synthesized with the presence of δC=N at 8.7 ppm of 1H-NMR and δC=N around 165 ppm of 13C-NMR. Metalation of phenoxy-imine ligand to oxo-vanadium moiety was indicated from ʋC=N at 1640 cm-1. Gas chromatography analysis indicated that epoxidation of 1-hexene gave new products, but allyl alcohol did not. Ab initio study of reaction mechanism with allyl alcohol as olefin model was conducted using Density Functional Theory (DFT) B3LYP and basis of set cc-pVDZ. Vibrational frequency of optimized catalyst structure was in agreement with experimental IR frequency. Calculated mechanistic insight showed that activation of molecular oxygen directly by olefin was both kinetically (ΔGǂ > 300 kJ/mol) and thermodynamically (ΔG > 300 kJ/mol) unpreferable. Molecular oxygen activated by catalyst by single electron transfer was thermodynamically more preferable than direct oxygen attact to olefin. Isomerization of η1-O2 complex to η2-O2 seemingly could undergo via small activation barrier (ΔGǂ = 12 kJ/mol). Bond breaking of two coordination bonding between glycidol product and catalyst at the last step seemed to be the rate determining step since it required the highest energy of all steps (ΔG = 228,17 kJ/mol). Energy involved in bond-breaking of epoxyhexane with catalyst (ΔG = 154 kJ/mol) was much smaller compared to that of glycidol. This step might be the reason why reaction of allyl alcohol with O2 in this study gave no product, while reaction of 1-hexene with O2 did.